2021
DOI: 10.51253/pafmj.v71i4.3136
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty and Discrimination Analysis of End of Term Multiple-Choice Questions at Community Medicine Department, Wah Medical College

Abstract: Objective: To perform post analysis of multiple-choice questions given in the 2nd term and send up examinations of the years 2016 to 2018, to establish relationship between difficulty (DF) and discrimination indices (DI) and to find out significant mean difference between the two. Study Design: Cross sectional study. Place and Duration of Study: Community Medicine Department, Wah Medical College, Wah, from Nov 2018 to Mar 2019. Methodology: A total of 390 Multiple-Choice Question of second te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The existing findings indicate a significant positive correlation between difficulty and discrimination indices ( p = 0.4, r = 0.30). Other authors have reported a significant linear and dome-shaped relationship between difficulty and the discrimination index [ 6 , 56 ]. These reports indicate that an increase in DI is associated with an increase in the discrimination index.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The existing findings indicate a significant positive correlation between difficulty and discrimination indices ( p = 0.4, r = 0.30). Other authors have reported a significant linear and dome-shaped relationship between difficulty and the discrimination index [ 6 , 56 ]. These reports indicate that an increase in DI is associated with an increase in the discrimination index.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the popularity of progress and exit tests necessitates using many test items. MCQs are the most commonly used tools in assessment because their reliability and validity are approved, and they can cover a large range of knowledge and knowledge [ 2 – 6 ]. The construction of high-quality MCQs type A has been reported to be difficult and time-consuming [ 4 , 7 – 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many assessment models have been proposed to evaluate the impact of online learning on students' learning achievements [10,11]. The difficulty index [12,13], discrimination index [14], distractor efficiency [15] and meta-analysis [16] were widely used to evaluate students' examination performance and learning achievements. The Open University in the UK indicated that compared to traditional on-site courses, online courses could save an average of 90% less energy and 85% fewer CO 2 emissions for each student [17].…”
Section: Introductionmentioning
confidence: 99%